EDUKASI KEBANGSAAN PEMILU DAMAI PEMILU DEMOKRATIS DI KELURAHAN KRATONAN TAHUN 2024 - Hidayat, M. Yunan; Usman, Taufiq; Sukari, S (Institut Islam Mamba'ul 'Ulum Surakarta, 2024)
Democracy is basically a state process based on the role of the people as the holder of supreme sovereignty. Democracy includes three basic principles: a state of the people, by the people, and for the people. that is, a legitimate government is a government that is recognized and supported by the majority of the people through democratic mechanisms such as general elections and exercises power on behalf of the people and the government in exercising its power is under the supervision of the people. Likewise in Indonesia, it will show a growth and development of maturity that should show an increasingly mature and beautiful face of Indonesian democracy. Democratic practices that prioritize social welfare and order will strengthen the character of a good nation state. Therefore, all levels of society must reject and prevent destructive political tactics so that economic efficiency and national stability are maintained throughout this year. Peaceful elections are the hopes and aspirations of all countries, including the Indonesian nation. Various activities, including education and discussions, were organized by domestic Indonesian actors with the aim of ensuring that the elections could be held smoothly without any obstacles or problems that could cause divisions in the country.